Enacting a place-responsive research methodology: walking interviews with educators. Issue 4 (1st October 2016) - Lynch, Jonathan; Mannion, Greg
ABSTRACT: Place-based and place-responsive approaches to outdoor learning and education are developing in many countries but there is dearth of theoretically-supported methodologies to take a more explicit account of place in research in these areas. In response, this article outlines one theoretical framing for place-responsive methodologies for researching outdoor learning and education. We exemplify how this might work in practice with data and analysis from one suggested place-responsive research method: the walking interview. Implications and consequences are explored for how outdoor learning might be researched more widely.